The association of mammographic density, age and positive family history with molecular subtypes among breast cancer patient in Hospital Universiti Sains Malaysia - Ismail, Siti Fitriwati Khazis (2021)
Introduction. Breast cancer is one of the commonest cancers among females. Multiple risk factors such as age, family history, mammogram density, and molecular subtypes are associated with the formation of breast carcinoma. Each factor causes the carcinogenesis of breast cancer in different mechanisms. Mammogram is one of the gold imaging modalities to diagnose breast cancer. Based on the imaging, a woman’s breasts can be categorised as non-dense and dense parenchyma. There is a clinically proven association between mammogram parenchyma density and breast cancer development. In addition, the prognosis of breast cancer is linked to the molecular subtypes, namely the “non-triple-negative” and “triple-negative” subtype depending on type of hormonal receptor that detected. To date, the association between molecular subtypes and the major risk factors of breast cancer is still poorly defined, especially among the Malaysian population. Therefore, the aim of this study was to assess the association between molecular subtypes with the mammogram density and other risk factors. Patients and methods. A cross-sectional study involving breast cancer patients of 18 years and above was conducted in the Hospital USM. Their mammogram and molecular subtype results were obtained. The mammogram was categorised as non-dense and dense while the molecular subtypes were divided into non-triple-negative and triple-negative. Other variables collected in this study were the patients’ age and family history of breast cancer. The proportion of non-dense and dense breasts among the patients was presented as descriptive analysis. The association between mammographic density, age, family history of breast cancer, and molecular subtype was tested using multiple logistic regression. esults. There were 280 participants in this study. The majority of them were Malays (n = 248, 98.6%) and aged 50 years and above (n = 220, 78.6%). Slightly more than half of them (n = 159, 56.8%) had non-dense breast. A high number of them reported no family history of breast cancer, (n = 246, 87.9%). Multiple logistic regression showed that the molecular subtypes of breast cancer was not significantly related to breast density, age, and family history of breast cancer. Conclusions. Based on the findings, breast density, age, and family history were not directly related to the molecular subtypes of breast cancer. Nonetheless, a case-control study with a larger sample size is recommended to obtain a more comprehensive understanding of the relationship between breast density, age, and family history with the molecular subtype of breast tissue.